2006
DOI: 10.1194/jlr.r600003-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

The sphingosine and diacylglycerol kinase superfamily of signaling kinases: localization as a key to signaling function

Abstract: The sphingosine and diacylglycerol kinases form a superfamily of structurally related lipid signaling kinases. One of the striking features of these kinases is that although they are clearly involved in agonist-mediated signaling, this signaling is accomplished with only a moderate (and sometimes no) increase in the enzymatic activity of the enzymes. Here, we summarize findings that indicate that signaling by these kinases is strongly dependent on their localization to specific intracellular sites rather than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
98
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 116 publications
(100 citation statements)
references
References 135 publications
2
98
0
Order By: Relevance
“…Future experiments should take intracellular distribution of sphingosine kinase proteins into account. While the activation of SphK1 leads to reduced apoptosis and improved proliferation, activation of SphK2 has been associated with enhanced cell death (Liu et al, 2003), which has been attributed to differential localisation in ER vs cytosol (Wattenberg et al, 2006). Neither SphK1 nor SphK2 has been detected in mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…Future experiments should take intracellular distribution of sphingosine kinase proteins into account. While the activation of SphK1 leads to reduced apoptosis and improved proliferation, activation of SphK2 has been associated with enhanced cell death (Liu et al, 2003), which has been attributed to differential localisation in ER vs cytosol (Wattenberg et al, 2006). Neither SphK1 nor SphK2 has been detected in mitochondria.…”
Section: Discussionmentioning
confidence: 99%
“…As for the activation of catalytic process by the enzyme on MVEs, it may mainly be regulated by its translocation of SphK2 from the cytoplasm to the membrane compartments of MVEs where the substrate sphingosine is enriched 51,52 , although direct enzyme activation, such as by phosphorylation 53 , may contribute to some extent. We have also shown that this continuous S1P signalling is indispensable to the cargo sorting into exosomal ILVs.…”
Section: Discussionmentioning
confidence: 99%
“…However, the signaling mechanisms responsible for BCR/ABL-induced regulation of Mcl-1 expression in CML cells remain unclear. Recently, sphingosine kinase-1 (SPK1), the enzyme that phosphorylates sphingosine to form sphingosine-1-phosphate (S1P), could be activated by a number of growth factors and intracellular oncoproteins, and has been proven to be involved in signal transduction (Duan et al, 2004;Granata et al, 2004;Wattenberg et al, 2006). SPK1 activation is involved in the multistep progression and multidrug resistance of leukemia (Le Scolan et al, 2005;Bonhoure et al, 2006).…”
mentioning
confidence: 99%